2016
DOI: 10.1177/0269215515623601
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to evaluate the feasibility of the Wii Fit for improving walking in older adults with lower limb amputation

Abstract: The results suggested the feasibility of the Wii.n.Walk with a medium effect size for improving walking capacity. Future larger randomized controlled trials investigating efficacy are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(125 citation statements)
references
References 38 publications
2
120
1
2
Order By: Relevance
“…The characteristics of included studies are shown in Table 2 : among the 19 studies, 8 were randomized clinical trials (RCTs), 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 2 were control trials (CTs; quasi-experimental pre–post-test design without randomization), 34 , 35 5 were 1-group pre–post-test designed studies (pre-experimental design with pre–post-test design among same participants), 36 , 37 , 38 , 39 , 40 and 4 were case studies (pre-experimental design with pre–post-test on 1 to 2 subjects only). 41 , 42 , 43 , 44 The USA was the primary location for AVG-based rehabilitation studies, 31 , 36 , 37 , 39 , 40 , 42 , 43 , 44 with 4 studies conducted in Canada, 26 , 27 , 28 , 34 2 in Brazil 29 , 35 and Australia, 32 , 41 and 1 in Singapore, 38 Turkey, 30 and Taiwan, China, 33 respectively. A majority ( n = 17; 89%) of the articles were published after 2010, and the oldest publication was in 2008, indicating that research on AVGs and rehabilitation is a young but expanding scientific field.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of included studies are shown in Table 2 : among the 19 studies, 8 were randomized clinical trials (RCTs), 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 2 were control trials (CTs; quasi-experimental pre–post-test design without randomization), 34 , 35 5 were 1-group pre–post-test designed studies (pre-experimental design with pre–post-test design among same participants), 36 , 37 , 38 , 39 , 40 and 4 were case studies (pre-experimental design with pre–post-test on 1 to 2 subjects only). 41 , 42 , 43 , 44 The USA was the primary location for AVG-based rehabilitation studies, 31 , 36 , 37 , 39 , 40 , 42 , 43 , 44 with 4 studies conducted in Canada, 26 , 27 , 28 , 34 2 in Brazil 29 , 35 and Australia, 32 , 41 and 1 in Singapore, 38 Turkey, 30 and Taiwan, China, 33 respectively. A majority ( n = 17; 89%) of the articles were published after 2010, and the oldest publication was in 2008, indicating that research on AVGs and rehabilitation is a young but expanding scientific field.…”
Section: Resultsmentioning
confidence: 99%
“… 27 (2011), Canada; to determine the effect of Wii Bowling game on measures of symptom intensity, enjoyment, and physical function in patients 10 males and 24 females aged 52–97 years with upper extremity dysfunction; intervention ( n = 19), control group ( n = 15); RCT Wii Sports (Bowling) Physical outcomes: improved functional ability and movement; psychological outcome: enjoyment; cognitive outcome: decreased pain intensity NHPPT, ROM, PACES, NPR 4–20 min per week for 4 weeks Participants improved on all outcomes after intervention, but only enjoyment of activity showed a significant difference between the standard exercise and Wii groups Imam et al. 28 (2017), Canada; to assess the feasibility of Wii.n.Walk in improving walking capacity in older adults 28 participants aged 50–78 years with lower limb amputation; intervention group ( n = 14); control group ( n = 14); RTC Nintendo Wii Fit (Wii.n.Walk) Physical outcome: improved walking capacity 2MWT 3–40 min per week for 4 weeks Improvement in walking capacity for intervention group, whereas the control group's performance declined Yong et al. 38 (2010), Singapore; to assess the feasibility of using the Nintendo Wii as an adjunct to conventional rehabilitation of patients 13 males and 7 females (mean age 64.5 years) with poststroke and upper limb weakness; pre–post-test design Wii Sports (Bowling, Boxing, Tennis, Golf, Baseball) Physical outcome: improved upper limb motor function; cognitive outcome: reduced upper limb pain FMA, MAS, VAS 6–30 min per week for 2 weeks Small but statistically significant improvements in FMA and Motricity Index Score; no significant improvements seen in MAS and VAS Mendes et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many possible applications of video games, either commercial or goal-oriented (“serious games”), in the fields of health and medicine were studied in the literature: promoting health behaviors [ 14 , 15 ], motor skills and balance [ 16 , 17 ], cognitive rehabilitation [ 6 , 18 ], medical training [ 19 , 20 ], and even psychotherapy [ 21 , 22 ]. As the literature indicates the possible negative outcomes of video games, and recurrent warnings are being published by leading medical authorities [ 23 ], clinicians and policy makers face a complex challenge: to translate the possibilities and applications of video games into clinical practice and official statements, in light of the confusing and contradictory evidence.…”
Section: Introductionmentioning
confidence: 99%